PREVALENSI INFEKSI NEMATODA USUS PADA PENDUDUK DESA BENTANGAN KECAMATAN WONOSARI, KABUPATEN KLATEN, JAWA TENGAH - PURWANINGSIH, S.; SUTIARTI, SUTIARTI; SUKAHAR, A.; SEDEMEN, IGP BADJRA (Research Center for Biology-Indonesian Institute of Sciences, 1988)
S. PURWANINGSIH, SUTIARTI. A. SUKAHAR & IGP BADJRA SEDEMEN.1988. Prevalence of intest Nematode infection at Bentangan,Kecamatan Wonosari-Klaten, Central Java.Berita Biologi 3(8):418 - 423.An experiment was conducted to study prevalence of intest Nematode infection at Bentangan, Kecamatan Wonosari-Klaten Central Java.Two hundred and ten persons were used in this experiment,they were gerabah makers,farmers and emphoyees, each group consisted of 70 persons.Samples of faeces was examined and identified by microscope.The result showed that were two types of intest Nematode found in the samples namely Ascaris lumbricoides and Trichuris trichiura. The prevalence of A.lumbricoides and T.trichiura infection did not correlate significantly with the type of occupation, sex, age, faeces density, method and intensity of the infection.